Viewers' Perception towards Advertisements on TV Media as a Promotional Strategy in the Current Marketing Scenario - Pongiannan, K. (Indian Journal of Marketing, 2011)
The present World revolves around the revolution of Information Technology. Economy is liberalized and industries are globalized. Regional marketing has been converted into global marketing. Because of these trends, it is the marketing which is affected to a very great extent. To overcome this challenge, many firms adapt several strategies to maintain their existence in the market. Among the several strategies, use of mass communication tools such as advertising, publicity, sales promotion and public relations are more essential. Moreover, every marketer must communicate with the present and prospective consumers about their products. The best way to serve the informational needs of consumers is through advertising, which is the most powerful and effective means of communication. Advertising is an inseparable aspect of product promotion. As a promotional strategy, advertising serves as a major tool in creating product awareness and persuades the potential consumers to take eventual purchase decisions. The effectiveness of a well-designed advertising message depends upon "when", "where" and "how" it is released. In short, the success of advertising depends upon the right selection of media, the timely release of the message, its frequency, continuity and reachability. Television is often called "The King" of the advertising media, since a majority of the people spend more hours in watching TV per day than any other medium. TV has proved its persuasive power in influencing human behavior from time to time because it combines the use of sight, color, sound and motion. Hence, this paper measures the perception of the viewers about the advertisements in TV media. The paper also provides suggestions to the marketers for sales promotion through effective advertising in TV media based on the viewers' perception.